Elucidating the hysteresis effect in printed flexible perovskite solar cells with SnO2 quantum dot- and PCBM-based electron transport layers - Yerassyl Yerlanuly; Erik O. Shalenov; Hryhorii P. Parkhomenko; Muhammad Salman Kiani; Zarina Kukhayeva; Annie Ng; Askhat N. Jumabekov (Heliyon)
Recently, flexible perovskite solar cells (FPSCs) fabricated using solution-processed printing techniques have garnered significant attention. However, challenges remain in achieving cost-effective, scalable manufacturing under ambient conditions and ensuring stable, efficient devices. This study focuses on fabricating printed FPSCs using the slot-die coating technique and examines the impact of SnO2 quantum dot (QD) and (6,6)-Phenyl C61 butyric acid methyl ester (PCBM) based electron transport layers (ETLs) on device performance and hysteresis. Experimentally results show that SnO2 QD-based devices exhibited favorable photovoltaic properties but significant hysteresis compared to PCBM-based devices. Numerical simulations have shown that the hysteresis effect in devices is influenced not only by the higher concentration of mobile ions in the perovskite layer of PCBM-based devices compared to SnO2 QD-based devices, but also by the more effective redistribution of these ions during forward and reverse J-V scans. The results provide insights into the behavior of printed FPSCs with different ETLs, contributing to the development of high-performance, hysteresis-free printed FPSCs.